PENGEMBANGAN MATERI PEMBELAJARAN TEKS DESKRIPSI BERBANTUAN WEB GOOGLE SITE UNTUK SISWA KELAS VII SMP SWASTA METHODIST LUBUK PAKAM TAHUN PEMBELAJARAN 2023/2024 - William T Sitorus (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research aims to determine the development process, form and feasibility of descriptive text learning materials assisted by the Googlesite website for class VII SMP students. This research uses the research and development (R&D) method with the ADDIE model which has been modified according to research needs and limitations. The stages carried out in this research process are analysis, design and development. The product assessment was carried out by two experts, namely a material expert and a media expert. The results of this research are based on (1) analysis of student needs and analysis of teacher modules, (2) the form of material integrated on the Googlesite website, (3) validation results from material experts. This learning material has the status of "very suitable for use" with an average score of 2, 69 and a score percentage of 89.41%. Furthermore, the media validation results were "very suitable for use" with an average score of 1.91 and a score percentage of 94%. So from the results of the research that has been carried out it can be concluded that the material developed is valid and suitable for use as supporting learning material for descriptive texts assisted by the Googlesite website.